A systematic review of research on reading in English on screen and on paper - Çetin, Kenan; Kılıçkaya, Ferit (Lingua Posnaniensis, 2019)
The introduction and wide use of devices, especially mobile ones, has changed the way learners read and do research for a variety of reasons, and this trend has attracted a number of studies conducted regarding reading on screen and on paper in addition to those dealing with the students’ behavior in using online resources to print ones. This paper aims at identifying the major findings and trends in reading research by describing the current state of knowledge and practice in the studies comparing reading on screen and on paper and to provide guidance for practitioners by analyzing and summarizing the existing research. The current review adopted a systematic review as the research methodology as well as the article selection and screening process. The articles published between 2009 and 2017 were reviewed, and 37 articles were included in the analysis. The review revealed that the research on onscreen and paper-based reading focused on comparing the learners’ performances in reading activities in both contexts and sharing preliminary findings and students’ views. However, the findings are inconclusive as mixed findings were produced as to the effects of reading on screen and on paper. Moreover, the review also indicates that practitioners are also interested in examining the factors and affordances in reading on screen. As a result, there is still further research needed to establish the factors affecting reading and comprehension while reading on screen and on paper.